2015
DOI: 10.1007/s10464-015-9758-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Disease, Social Support, and Perceived Health: A Lifespan Approach

Abstract: We examined the relationship between the cumulative presence of major disease (cancer, stroke, diabetes, heart disease, and hypertension), social support, and self-reported general and emotional well-being in a community representative sample of predominantly White and African American respondents (N = 1349). Across all ages, greater presence of disease predicted poorer reported general health, and predicted lower emotional well-being for respondents 40 and above. In contrast, social support predicted better-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 58 publications
6
42
0
4
Order By: Relevance
“…After adjusting for several previously identified confounding variables, the findings show a moderating effect of race on the relationship between cancer history and emotional distress, with African American cancer long-term survivors experiencing significantly higher levels of emotional distress compared to the general cancer and non-cancer populations. Consistent with previous studies, the study also found associations between socio-demographic factors [7], physical health [20], self-efficacy [11,21], optimal lifestyle behaviors [22][23][24], and emotional distress.…”
Section: Discussionsupporting
confidence: 90%
“…After adjusting for several previously identified confounding variables, the findings show a moderating effect of race on the relationship between cancer history and emotional distress, with African American cancer long-term survivors experiencing significantly higher levels of emotional distress compared to the general cancer and non-cancer populations. Consistent with previous studies, the study also found associations between socio-demographic factors [7], physical health [20], self-efficacy [11,21], optimal lifestyle behaviors [22][23][24], and emotional distress.…”
Section: Discussionsupporting
confidence: 90%
“…For example, living in a high-income neighborhood is related to greater social integration among neighbors (Marcus, Echeverria, Holland, Abraido-Lanza & Passannante, 2015). In turn, social support from community members is protective for physical and emotional well-being (Heinze, Kruger, Reischl, Cupal & Zimmerman, 2015). Finally, it is possible that the findings are driven by selection; low-income individuals who are healthier may be better equipped to secure housing in high-income neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of social support is interpersonal interactions with others that can lead the positive feelings such as feeling loved, close, safe, belonging to a group, and providing emotional, physical, and information assistance (15). Social support covering three elements, namely, emotional, instrumental, and information (16).…”
Section: Factors Associated With Caregiver Burden 1 Social Supportmentioning
confidence: 99%
“…Sources of social support can come from friends, children, family members, and partners (17). The sources of social support can come from partners, children, family, friends, neighbors, and community members (16). Social support plays a vital role throughout a person's life.…”
Section: Factors Associated With Caregiver Burden 1 Social Supportmentioning
confidence: 99%
See 1 more Smart Citation